Biosecurity practices on small-ruminant farms in five Turkish provinces: a cross-sectional survey with multiple correspondence analysis - Mil-Homens, Mafalda Pedro; Georges, Ipek Keskin Fernandez; Raizman, Eran; Beltrán-Alcrudo, Daniel; Allepuz, Alberto (Frontiers in Veterinary Science, 2025)
IntroductionA cross-sectional biosecurity survey was conducted in Türkiye to assess practices in small ruminant farms across five provinces.MethodsA total of 364 breeders were interviewed on farm management, health practices, animal purchase and movement, and dead animal disposal. Breeders were selected based on small ruminant density, breed diversity, primary income source, presence of commercial enterprises, and branding potential. Among participants, 332 responses were eligible for analysis. Descriptive statistics and Multiple Correspondence Analysis (MCA) were used.ResultsThe most commonly administered vaccines were for sheep pox (193/332, 58%), foot-and-mouth disease (175/332, 53%), and brucellosis (129/332, 39%). About 58% (195/332) reported direct contact with ruminants from other herds, 30% (101/332) shared vehicles or equipment, 59% (196/332) attended live animal markets, and 99% (328/332) purchased animals, yet 67% (222/332) did not quarantine and only 14% (46/332) considered health status before purchase. Dead animals were buried (129/332, 39%) or fed to dogs (30/332, 9%). MCA indicated biosecurity improvements were needed across provinces, education levels, herd sizes, and production types.DiscussionThe high proportion of direct contacts highlights the need for community-based interventions, shared quarantine facilities, physical barriers, and targeted training on disease recognition, disinfection, and record-keeping to strengthen herd health.